Jathropha foliage sustains soil nutrients level and grain yiled of pearl millet in Sudan Savannah (Nigeria) - Abdullahi Aliyu, Nuraddeen; Ismail, Roslan; Yusoff, Martini Mohammad; Mohd Anuar, Mohd Firdaus; Garba K / Naisa, Adamu (Association of Indian pharmacist-AIP, Published by ResearchTrentz, 2023)
Field experiments were conducted in the year 2020 and 2021 rainy seasons to evaluate the soil nutrients level and grain yield of pearl millet in response to Jatropha foliage (organic soil amendment), at Kadawa (11.650° N and 8.450° E) Nigeria, where accessibility and affordability of fertilizer is difficult to low income farmers who cultivate crops on low fertility soils. To improve the fertility of the soils, there is need to apply large amounts of organic materials such as Jatropha foliage, which is a cheap and available resource in the study area. The treatments were: T1 (control), T2 (5 t/ha Jatropha foliage), T3 (10 t/ha Jatropha foliage) and T4 (Full recommended rate of fertilizer) arranged using Randomized Complete Block Design (RCBD) with 3 replications. From 2020 to 2021, there were increases in mean Organic Carbon (0.36-0.46), Available Phosphorus (5.45-10.01 mg/kg), exchangeable Potassium (0.12-0.14 cmol/kg) and Grain yield (1684.6-1741.8 kg/ha). These increases were attributed to the carryover effect of nutrients from previous year’s application (2020-2021 wet seasons). Application of 10t/ha Jatropha foliage significantly increased the grain yield by 34.2-44.6 over control treatment. The full recommended rate of fertilizer (Full-RF) was significantly superior to the 10 t/ha rate of Jatropha foliage in improving the grain yield of pearl millet by 81.1-83.2. However, inorganic fertilizer caused a decline in soil available P, exchangeable K, CEC and pH. Therefore, application of Jatropha foliage is recommended to sustain soil fertility and grain yield of pearl millet in the Nigerian Sudan Savannah.